2015
DOI: 10.1051/epjconf/201510106036
|View full text |Cite
|
Sign up to set email alerts
|

Long term light curve variations of theKeplerCepheid V 1154 Cyg

Abstract: Abstract. We present a period analysis of the light curve and its Fourier parameters of the bright Cepheid V1154 Cyg (P=4.925454 days) based on the observations by the Kepler space telescope. Fourier parameters R 21 , R 31 clearly indicate variations with a period of 158.2 ± 1 days (more than 5σ peak in the power spectrum) with a very small amplitude (0.265-0.275 for R 21 , 0.065-0.071 for R 31 ) making impossible to detect it with groundbased observations. Finally we discuss that this effect is similar to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
2
4
1
Order By: Relevance
“…3.1). Our findings agree with the period calculated from smoothed Fourier parameters by Kanev, Savanov & Sachkov (2015). The frequency spectrum of R21 is shown in the top panel of Fig.…”
Section: Fourier Parameterssupporting
confidence: 90%
See 1 more Smart Citation
“…3.1). Our findings agree with the period calculated from smoothed Fourier parameters by Kanev, Savanov & Sachkov (2015). The frequency spectrum of R21 is shown in the top panel of Fig.…”
Section: Fourier Parameterssupporting
confidence: 90%
“…The latest study of V1154 Cyg was performed by Kanev, Savanov & Sachkov (2015) using the 4 years of long cadence Kepler data and studied the light curve by using Fourier decomposition technique. They found that the Fourier parameters R21 and R31 (see in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…Such single periodicity may be due to contamination, but may also indicate a possible modulation. We note that periodic modulation was detected in V1154 Cyg, fundamental mode Cepheid (P0 ≈ 4.925 d) observed with Kepler/K2 (Kanev, Savanov & Sachkov 2015;Derekas et al 2017). Modulation period is Pm ≈ 159 d, but amplitudes of the modulation side peaks are nearly an order of magnitude lower than reported here; the highest side peak, at ν0 − νm, has an amplitude of 0.55 mmag.…”
Section: Discussioncontrasting
confidence: 43%
“…An early example of this was V473 Lyr, which exhibits periodic variations of its light and radial velocity amplitude, similar to RR Lyrae stars exhibiting the Blazhko effect (Burki et al 1982;Molnár et al 2013). Space-based photometry obtained with the Kepler, MOST, and BRITE satellites has revealed a host of variations in the fundamentalmode Cepheid V1154 Cyg (Derekas et al 2012;Kanev et al 2015;Derekas et al 2017), found long-period modulation in T Vul (Smolec et al 2016a) and suggested a greater degree of irregularity exhibited by first-overtone (FO) Cepheids (Evans et al 2015). Smolec (2017) detected strictly periodic modulations in the pulsation periods of 51 Magellanic Cloud Cepheids using OGLE data.…”
Section: Introductionmentioning
confidence: 98%